Analisis Penentuan Harga Pokok Produksi dengan Metode Full Costing dan Penentuan Harga Jual dengan Pendekatan Cost Plus Pricing pada UMKM Es Teh Solo Cabang Rawalumbu Kota Bekasi - Vina Sofiana; Qori Erna Lestari; Stefani Afrida; Evi Mahaerani (Universitas 45 Surabaya, 2024)
The food and beverage industry in Indonesia is growing rapidly, with iced tea being one of the most popular products. However, in running an iced tea business, the right strategy and method are needed to analyze the cost of goods manufactured (HPP) so that the product can compete with competitors and remain profitable. This study analyzes the application of the full costing method for calculating the Cost of Goods Sold (HPP) and cost plus pricing to determine the selling price at the Es Teh Solo UMKM Rawalumbu Branch, Bekasi City. The results showed that the company's HPP was IDR 1,800 per serving, different from the researcher's calculation of IDR 1,854 per serving because it did not take into account overhead costs. The company's selling price of IDR 4,000 per serving does not reflect a profit margin of 45%, with an ideal price of IDR 4,120 per serving. Optimizing the calculation of HPP is needed to improve the accuracy of selling prices, profitability, and competitiveness.